High Sensitivity Prototype Kit with IoT System for Fire Detection in a Peatland Swamp Forest Area - Hamzah, Shipun Anuar; Dalimin, Mohd Noh; Md Som, Mohamad; Utomo, Wahyu Mulyo; Zainal, Mohd Shamian; Yusoff, Nor Azizi; Ramli, Khairun Nidzam; Talib, Rahmat; Mustapa, Mohammad Sukri; Abd Jamil, Ansar; Sanusi, Mohd Hamim; Sidek, Azmi (International Journal of Integrated Engineering, 2023)
Smoke sensor of the photoelectric type is often used in indoor fire detection system. It is very sensitive to fire smoke and will trigger a fire alarm quickly when the presence of smoke is detected. By making a small innovation, this sensor can be implemented outdoors by means of IoT as used in the forest fire early detection system. However, the typical use of the sensor without any modification causes the sensitivity of the system to be very low such as failing to identify the actual presence of smoke. To increase the sensitivity of systems that use this type of sensor, the developed system is equipped with an automatic reclosing operation that is able to distinguish real smoke or not. The system has been designed to trigger cloud servers only after detecting smoke for ten seconds or beyond. System equipped with automatic reclosing operation show better response by not triggering cloud servers when detecting temporary smoke from car, motorcycle or nearby factory. When comparing the system before and after using this operation is, it was found that the system no longer sends smoke notification message to the user via Telegram channel when this temporary smoke is detected